EFEKTIVITAS MEDIA VIDEO TERHADAP PENGETAHUAN ANTIBIOTIK DI KECAMATAN MENDO BARAT KABUPATEN BANGKA - Hesty; Lana Sari; Dela Lanaya (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2025)
Antibiotics are drugs used to prevent and treat infections caused by bacteria, but there is still a lot of inappropriate use of antibiotics. Inaccurate use of antibiotics increases the risk of antibiotic resistance, namely, bacteria becoming resistant to antibiotics. One effort to increase knowledge related to antibiotics is to use video media. Providing digital health information and education with video media is more effective and innovative than other methods. The technique used in this research is quantitative analytic with a one-group pretest-posttest design. Retrieval of data in research using an accidental sampling technique. The number of samples in the study was 394 respondents. The measuring instrument used in the study was a questionnaire given to the people sampled using video media in two pretest and posttest measurements. The study results showed significant differences in changes in knowledge before and after giving knowledge related to antibiotics using video media with a p-value = (0.001 < 0.05). Video media effectively increases the understanding of the people of the West Mendo District about antibiotics.